Oral Lipoma In Elderly Saudi Patient: A Case Report - Ikram, Rashad Ikram; Al-Eid, Abdul Aziz Abdul Rehman (International Journal of Health Sciences, 2012)
Lipomas are relatively uncommon benign tumor occurring in the oral cavity with a prevalence rate of 1% to 4% of all oral lesions. They present as a slow growing, painless, asymptomatic submucosal mass and surgical excision is the treatment of choice. Oral lipomas have been known to grow to large sizes causing interference with speech, mastication and construction of denture. A case of 77 years old male patient with lipoma of buccal mucosa in oral cavity which exhibited a sudden growth after a lag time of 3 years with mastication and speech difficulties. The tumor excised in total with restoration of normal speech and mastication. Keywords: Oral Lipoma, Benign Tumor, Case Report